Speciation of a subterranean amphipod on the glacier margins in South Eastern Alps, Europe. (9th November 2021) - Delić, Teo; Trontelj, Peter; Zakšek, Valerija; Brancelj, Anton; Simčič, Tatjana; Stoch, Fabio; Fišer, Cene
Abstract: Aim: Climatic oscillations altered distributions through migration, extinction, adaptation or speciation. Their joint effect has been rarely studied. Here, we tested how Pleistocene climatic oscillations shaped the evolutionary history and distribution of a subterranean amphipod. We tested four predictions for extant populations: (i) populations of good dispersers moving along the ice‐sheet margin should have homogenous genetic structure and broad tolerance to temperatures; (ii) adaptation to local temperatures evolved in poor dispersers with spatially structured populations; (iii) Pleistocene extinctions in the range of historical glaciers should reflect founder effects and high sensitivity to low temperatures; (iv) para‐ or allopatric speciation could unfold through diverse scenarios as a response to local adaptation and constrained dispersal. Location: North‐Western part of the Balkan Peninsula, Europe. Taxon: Niphargus stygius, Amphipoda, Crustacea. Methods: We used time‐calibrated multilocus phylogenies and multilocus delimitations to test independently evolving lineages. For each lineage, separately we assessed historical population dynamics and dispersal potential, modelled climatic niches and mapped them onto palaeoclimatic maps. Additionally, we conducted enzymatic and respiratory tests of thermal tolerance, and reconstructed historical distribution range using phylogeographical diffusion analyses. Results: We identified four independently evolving tentative species, dated to the Pleistocene, with no evidence of extinction events. Three main lineages are parapatric with few pairwise syntopies and no traces of hybridization. They evolved in allopatry and possibly maintained constant effective population sizes. The lineages are phylogeographically substructured, indicating low recent dispersal. They differ in their climatic niche envelopes and physiological responses to unfavourable temperatures. Main conclusions: We infer that periodic drops of groundwater in the Pleistocene caused two vicariant events and the onset of two allopatric speciation events, followed by phases of dispersal leading to secondary contact and occasional overlap of ranges. Speciation was seemingly fostered by eco‐physiologically differentiation due to adaptation to local climates.